Organoid-Transplant Model Systems to Study the Effects of Obesity on the Pancreatic Carcinogenesis in vivo - Lupo, Francesca; Piro, Geny; Torroni, Lorena; Delfino, Pietro; Trovato, Rosalinda; Rusev, Borislav; Fiore, Alessandra; Filippini, Dea; De Sanctis, Francesco; Manfredi, Marcello; Marengo, Emilio; Lawlor, Rita Teresa; et al. (Frontiers in Cell and Developmental Biology, 2020)
Pancreatic ductal adenocarcinoma (PDAC) is the third leading cause of cancer-related mortality among adults in developed countries. The discovery of the most common genetic alterations as well as the development of organoids models’ of pancreatic cancer has provided insight into the fundamental pathways driving tumour progression from a normal cell, to non-invasive precursor lesion, to widely metastatic disease, offering new opportunities for identifying the key driver of cancer evolution. Obesity is one of the most serious public health challenges of the 21st century. Several epidemiological studies have shown the positive association between obesity and cancer-related morbidity/mortality, as well as poor prognosis and poorer treatment outcome. Despite strong evidence indicates a link between obesity and cancer incidence, the molecular basis of the initiating events remains largely elusive. This is mainly due to the lack of an accurate and reliable model of pancreatic carcinogenesis that mimics human obesity-associated PDAC, making data interpretation difficult and often confusing. Here we propose a suitable and manageable preclinical tool, organoids-based, to study the effects of obesity on pancreatic carcinogenesis. Therefore, we tracked the effects of obesity on the natural evolution of PDAC in a genetically defined transplantable model of the syngeneic murine pancreatic preneoplastic lesion (mP) and tumour (mT) derived-organoids that recapitulates the progression of human disease from early preinvasive lesions to metastatic disease. Our results suggest that organoid-derived transplants in obese mice represent a suitable system to study early steps of pancreatic carcinogenesis and support the hypothesis that inflammation induced by obesity stimulates tumour progression and metastatization during pancreatic carcinogenesis.